First Endoscopic-Guided Percutaneous Nephrolithotomy (ePSL) with Prone Split-Leg Position in Manado - Phoebus, Andrien; Astram, Ari; Toreh, Christof; Arianto, Eko; Wihono, Frendy (e-CliniC, 2025)
Abstract: Literature has not yet defined the best position for percutaneous nephrolithotomy (PCNL) based on the complexity of the stone burden. This case of left-sided complex kidney stones underwent endoscopic-guided PCNL in an PSL (prone split-leg position). A 61-year-old woman with a chief complaint of right pelvic pain. Standard prone PCNL was planned for this patient, however, due to so much debris in the pelviocalyceal system during URS evaluation and ureter catheter insertion, we decided to puncture with ultrasound guidance rather than fluoroscopy. Intraoperatively there was residual superior calyx stone that was beyond the reach of nephroscope. We decided not to do a double puncture because of poor vision due to the floating debris. In the second procedure, the ePSL method was utilized. A C-arm and nephroscope examination revealed no active bleeding, no infundibulum laceration, and no remaining stones. The primary goals of this method were to remove stones from the urinary tract throughout the entire tract using a one-step, one-access procedure that made the most of the full range of endourologic equipment. There were a number of reasons why the prone split-leg position was chosen, including operator preference, familiarity with the position, and the inability to make a direct puncture in the upper pole. The main drawback was that patient would not be able to see how well and safely this method worked over time. In conclusion, complex kidney stones can be treated with ePSL performed in the prone split-leg position, which is a safe procedure with a low risk of complications. Keywords: percutaneous nephrolithotomy; prone split-leg position; complex kidney stones